2021
DOI: 10.1186/s13023-021-02117-4
|View full text |Cite
|
Sign up to set email alerts
|

The development of early social cognitive skills in neurogenetic syndromes associated with autism: Cornelia de Lange, fragile X and Rubinstein–Taybi syndromes

Abstract: Background Cornelia de Lange (CdLS), Fragile X (FXS) and Rubinstein–Taybi syndromes (RTS) evidence unique profiles of autistic characteristics. To delineate these profiles further, the development of early social cognitive abilities in children with CdLS, FXS and RTS was compared to that observed in typically developing (TD) and autistic (AUT) children. Methods Children with CdLS (N = 22), FXS (N = 19) and RTS (N = 18), completed the Early Social C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(9 citation statements)
references
References 75 publications
0
9
0
Order By: Relevance
“…These findings, along with reports of prolonged eye gaze and heightened social anxiety in CdLS (Collis et al, 2006; Goodban, 1993), suggest that the profile of social impairments in CdLS may be different to that observed in ASD. With regard to RTS, recent research conducted following this review has indicated the benefit of examining autism characteristics and social characteristics at this level of fine‐grained description indicating nuanced differences to those observed in ASD (Adrien et al, 2021; Ellis et al, 2021; Taupiac et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…These findings, along with reports of prolonged eye gaze and heightened social anxiety in CdLS (Collis et al, 2006; Goodban, 1993), suggest that the profile of social impairments in CdLS may be different to that observed in ASD. With regard to RTS, recent research conducted following this review has indicated the benefit of examining autism characteristics and social characteristics at this level of fine‐grained description indicating nuanced differences to those observed in ASD (Adrien et al, 2021; Ellis et al, 2021; Taupiac et al, 2021).…”
Section: Discussionmentioning
confidence: 99%
“…With the illustrative examples detailed above, one can differentiate between an individual who is capable of managing his/her emotional states and an individual who is at risk of social anxiety (i.e., social value). Once differentiated, one might propose a rehabilitative intervention with further experimental conditions (i.e., see above) to promote adaptive responding and constructive engagement in individuals with FXS (Caffò et al, 2016 ; Raspa et al, 2020 ; Ellis et al, 2021 ). To enhance the reader's ability to follow the logic with each possible outcome, we inserted a graphical representation of the proposed functioning in Figure 1 .…”
Section: How Should It Workmentioning
confidence: 99%
“…Neurodevelopmental disorders such as autism spectrum disorder (ASD), intellectual disability (ID), and developmental delay, are common neurological conditions affecting the typical developmental trajectory [ 1 ]. With the rise of readily available genetic testing and the increasing awareness of treatable causes for ID [ 2 ], the recognition of genetic etiologies among these common conditions is increasing, including the identification of monogenic etiologies [ 3 , 4 ]. Further, next generation sequencing techniques have allowed for discovery of new disease-causing genes, necessitating re-analysis of exome data over time.…”
Section: Introductionmentioning
confidence: 99%